Assessing Motivational Interviewing through Co-Active Life Coaching Tools as a Smoking Cessation Intervention: A Demonstration Study - Tara Mantler; Jennifer D. Irwin; Don Morrow (International Journal of Evidence Based Coaching and Mentoring, 2010)
The objective of this study was to explore smoking triggers and obstacles to cessation, and intervention experiences among nine 19-28 year old smokers who participated in a 3-month coaching-administered Motivational Interviewing (MI) intervention. In addition to qualitative methods, quantitative trends regarding self-efficacy, self-esteem, cigarette dependency, and average daily cigarettes use were assessed via a repeated measures design. Participants engaged in 9 sessions with a certified coach over 3-months. In-depth interviews and previously validated quantitative assessments were conducted at baseline, 1, 3, and 6-months. Qualitatively, stress and social situations were primary smoking triggers. Cessation obstacles were a sense of personal identify as a smoker and feeling controlled by cigarettes. Through the intervention participants reportedly gained: personal insights related and unrelated to smoking; helpful ways to cope with smoking challenges; and heightened awareness about other choices. Quantitatively, all constructs’ trends supported qualitative findings. The application of motivational interviewing using coaching tools is valuable for reducing smoking, and for providing smokers’ with insights about their behaviours, their triggers, and what they need to be and stay smoke-free. Additional research with a larger sample over a longer time is warranted.